Von Willebrand Factor as a Novel Player in Valvular Heart Disease: From Bench to Valve Replacement. (February 2018) - Gragnano, Felice; Crisci, Mario; Bigazzi, Maurizio Cappelli; Bianchi, Renatomaria; Sperlongano, Simona; Natale, Francesco; Fimiani, Fabio; Concilio, Claudia; Cesaro, Arturo; Pariggiano, Ivana; Diana, Vincenzo; Limongelli, Giuseppe; et al.
Von Willebrand Factor (vWF) is a well-known mediator of hemostasis and vascular inflammation. Its dynamic modulation in the bloodstream, according to hemodynamic conditions, makes it an appealing biomarker in patients with valvular heart disease (VHD). Recent studies highlight the close connection between vWF and VHD, with possible implications in the pathogenesis of VHD, promoting valve aging and calcification or favoring the development of infective endocarditis. Moreover, vWF has been recently proposed as a new diagnostic and prognostic tool in patients with valve stenosis or regurgitation, showing a strict correlation with severity of valve disease, outcome, and bleeding (Heyde syndrome). A novel role for vWF is also emerging in patients undergoing percutaneous or surgical valve repair/replacement to select and stratify patients, evaluate periprocedural bleeding risk, and detect procedural complications. We also report our single-center experience, suggesting, for the first time, possible clinical implications for vWF in percutaneous mitral valve repair (MitraClip). This review summarizes recent advances in the role of vWF in VHD with an updated overview going from bench to operating room.